1979
DOI: 10.1136/adc.54.12.946
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of caffeine elimination in infancy.

Abstract: SUMMARY The developmental changes in caffeine elimination were studied in 7 infants aged between 21 weeks and 6 months. Adult plasma clearance rate of caffeine was achieved at 3 to 41 months of age. Plasma half-life and elimination rate reached adult levels after 3 to 41 months and seemed to exceed adult capacity thereafter. No significant changes in apparent volume of distribution were noted. Our data provide some indication of the age in infancy when the low rates of caffeine elimination in the neonate incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(67 citation statements)
references
References 24 publications
5
62
0
Order By: Relevance
“…One study reported that the alerting effect of coffee lasted between 5.5 and 7.5 h in two different experimental groups [33], which is consistent with the 3 to 5 h half-life of caffeine among adults. Some data suggest that the half-life of caffeine is much longer for pregnant women and for newborns [29]; in infants it decreases gradually with age during the first year to the adults' norm [34]. No studies examining the effects of caffeine on sleep patterns of infants and toddlers were found in the literature.…”
Section: Introductionmentioning
confidence: 93%
“…One study reported that the alerting effect of coffee lasted between 5.5 and 7.5 h in two different experimental groups [33], which is consistent with the 3 to 5 h half-life of caffeine among adults. Some data suggest that the half-life of caffeine is much longer for pregnant women and for newborns [29]; in infants it decreases gradually with age during the first year to the adults' norm [34]. No studies examining the effects of caffeine on sleep patterns of infants and toddlers were found in the literature.…”
Section: Introductionmentioning
confidence: 93%
“…In the newborn it is close to 4 days (Aldridge et al 1979;Aranda et al 1979). By the age of 3-4 ½ months, caffeine's half-life in plasma is down to about 14 hours, and is further reduced to 2-3 hours by the age of 5-6 months ).…”
Section: Pharmacokinetics Of Caffeinementioning
confidence: 95%
“…Around 7% of this 18% would be caffeine. Aranda et al (1979a) and reported slightly lower estimates for caffeine. Since the demethylated metabolites of caffeine possess considerable pharmacological activity (Soyka, 1979;Karlsson et al, 1985), and the newborn may accumulate methyl-xanthines due to the slow metabolism of particularly caffeine, the impact of their ingestion by the newborn following maternal caffeine should be addressed further (Oo et al, 1995).…”
Section: Methylxanthine Exposure Of the Newbornmentioning
confidence: 99%
“…The reason for these variations are probably immature, inhibited, or induced biotransformation systems. For references to original articles on this subject, see Aranda et al (1979a), ACSH (1981), von Borstel (1983, Brazier et al (1983), Yesair et al (1984) and . A "normal" concentration of caffeine in tissues of consumers of caffeinecontaining beverages has been found to be in the range 0.2-2 µg/ml (von Borstel, 1983).…”
Section: Absorption and Distribution In Manmentioning
confidence: 99%